Numerical relation and 3D modelling of human head balance factors / Vahid Goodarzy - Vahid, Goodarzy (2016)
The visual, vestibular, and proprioceptive systems make up the physiological balance sensory system which is essential in maintaining balance and stability of a human body. In biomechanical analysis, forces around the centre of gravity affect movement and stability. The head centre of gravity (CG) which crosses three main planes (sagittal, frontal and transverse) is an important area related with balance. Previous researches have associated the head sensory systems with balance, however mathematical relations between these balance factors and CG have not been established. The main aim of the study was to establish mathematical relation using distances and angles between the head sensory systems (visual and vestibular) and CG, and used these values to design a novel 3D model of a human head. The secondary aim of the study was to introduce photography (PH) as a new technique to locate the head sensory system’s anatomical landmarks and validate this using computer aided tomography (CT). Three methods were employed; (i) CT - to locate the CG and exact anatomical location of visual and vestibular systems, (ii) PH - to locate the surface anatomical landmarks of head sensory systems, and (iii) anthropometric devices to calculate the head volume. In order to calculate the mathematical relationships between the head sensory systems, the balance factor line (BFL: the line connecting visual and vestibular systems) was illustrated. The average distance between the visual and vestibular lines (DVV) on both sides; for CT and PH are 8.16 ± 0.35 cm, and 8.11 ± 0.58 cm respectively, while the angle between the BFL and the Frankfort plane (AVVF) on both sides; for CT and PH are 11.80 ± 0.25o, and 11.65 ± 0.45o respectively. The comparison for angle of AVVF between left and right sides has r value of 0.98, while P < 0.001. These values showed that there was no significant difference between CT and photos. The intraclass correlation coefficient between two ratters which shows the reliability of the methods was 0.970 for the CT images and 0.960 for PH. Based on the 3D modelling, an imagery plane which connects the left and right head balance factors was drawn. The head CG was represented as a hollow sphere in this model, and the connection between the CG and the imaginary plane formed pyramidal structure. CT scan imaging is hazardous and expensive and also the equipment is not easy to access, thus, this new method is hypothesised as a viable alternative compared to previous approaches that yield outcomes similar to those of the CT images. The proposed imaginary plane connecting the human balance factors is not parallel with the existing planes. Applying this new 3D model of the human head, the mathematical relationships between the head CG and the imaginary plane could be used in biomechanical analysis of human balance and stability.